Design and Development of an E-Commerce Website Using the Waterfall Method with the Laravel Framework - Gema Parasti Mindara; Aisya Tyanafisya; Siti Farah Fakhirah; Azhar Nadhif Annaufal; Ibnu Aqil Mahendar; Aditya Wicaksono (Universitas Islam Kuantan Singingi, 2025)
The e-commerce sector has experienced significant growth in Indonesia in recent years. However, many small business owners still rely on manual operations through social media platforms. This study focuses on the design and implementation of an e-commerce website for Comot Langsung, a local thrifting business, using the Waterfall methodology and the Laravel framework. The sequential nature of the Waterfall method is applied through six phases: requirement analysis, system design, development, testing, deployment, and ongoing maintenance. In the analysis phase, several key features were identified, including user registration, product catalog, shopping cart, ordering system, and QRIS payment integration. The design process utilized UML diagrams to clearly and structurally visualize the system architecture and user flow. The results show that all features were successfully implemented, offering high responsiveness and ease of navigation. This website is expected to expand market reach for thrifting entrepreneurs while enhancing the online shopping experience for consumers in selecting and purchasing vintage fashion products efficiently and conveniently.